Las técnicas de enseñanza utilizadas por los docentes para la resolución de problemas y su incidencia en el aprendizaje de la física, en los estudiantes de primero y segundo año de bachillerato general unificado del colegio de bachillerato “Hernán Gallardo Moscoso”, de la ciudad de Loja, periodo académico septiembre 2018 – mayo 2019”. Lineamientos alternativos - Cueva Arrobo, Juan Gabriel (2020)
The realization of this research work arises from the need to respond to the problem raised which seeks to give an explanation about the teaching techniques used by the teacher in solving physics problems and the impact they have on the desired learning reach in students throughout the educational process. The general objective of the following research work is: to analyze the teaching techniques used by teachers to solve problems and their impact on the learning of physics by the first and second year students of the Unified General Baccalaureate in the High School "Hernan Gallardo Moscoso", during the academic period September 2018 - May 2019. For the execution of this work, 60 students from BGU, first and second year and two teachers from the institution were found, referring to the knowledge about the teaching techniques used in the class; after that a pre-test was applied to the students to measure the level of learning, these results allowed to determine the low knowledge acquired in the subject; giving an arithmetic mean for the students of first BGU an average of 5.47 / 10 and of 5,39 / 10 for the second BGU, that is why during the investigation the use of new techniques for the resolution of physics problems was socialized with the teacher, to subsequently apply the post-test where the averages obtained were 6, 94/10 for the first BGU and 7.64 / 10 for the second BGU, these results allowed us to verify the hypothesis raised and, in turn, develop an alternative approach that allows teachers to improve the quality of the teaching-learning process.